A Study of Metastatic Lesion of Lymph Node by Fine Needle Aspiration Cytology - Rathod, Kirti M; Shah, Smita A (National Journal of Community Medicine, 2012)
Purpose: Purpose of the study is to study the pattern of presentation of metastatic lesions of the peripheral lymph nodes for various malignant tumors and for confirmation of metastatic lesions in cases of a known or an occult primary. Methods: Total 140 cases of metastatic lesions of the lymph node were studied from January 2003 to December 2004 by Fine Needle Aspiration Cytology in cytology department of B.J.Medical college, Ahmedabad. Results: Squamous cell carcinoma was the most common metastatic lesions of the lymph node and comprised about 80%. Metastatic lesions of lymph node occur more commonly after age of 40 years and more common in male than female except metastatic lesion form carcinoma of breast .Cervical lymph nodes were common site for metastasis for squamous cell carcinoma and axillary lymph nodes were common site for metastasis from breast malignancy. Conclusion: FNAC is cost-effective, reliable, rapid and inexpensive procedure in diagnosis of lymphadenopathy. Metastatic lesions confirmed by FNAC also give a clue to the nature and site of primary.